KINERJA APARAT DESA DALAM PENYELENGGARAAN PEMERINTAH DESA RIBANG KECAMATAN MUARA UYA KABUPATEN TABALONG (Studi pada Kaur Pemerintahan) - Wahyu Subadi (Jurnal PubBis, 2019)
The purpose of this study was to find out and analyze: 1) the performance of Village Officials in administering the government, especially at the research location; 2) factors that hamper the performance of Village Officials in administering the government at the research site.Data collection techniques in this study are: 1) Observation; 2) Interview; and 3) Documentation. Interviews are the main instrument, namely with key informants such as the Village Head, Head of Government and Community for making results in the discussion.The results showed that: The Performance of Village Officials in Administering the Government of Ribang Village in Muara Uya sub District, Tabalong Regency (Study of Government Affairs) can be said to run well and factors that inhibit performance are lack of ability to operate computers and lack of motivation from the apparatus to achieve work goals. Suggestions, for the implementation of services in the framework of organizing village governance, the Village Head and Village Officials need to carry out their work functions and duties to the maximum to better serve the community and Need learning or courses for Village Officials who are not yet proficient at using computers. Keywords: performance; village officials and government administration